Network formation with endogenous decay - Francesco Feri (University of Innsbruck, Department of Public Finance, 2007)
This paper considers a model of economic network characterized by an endogenous architecture and frictions in the relations among agents as described in Bala and Goyal (2000). We propose a similar network model with the difference that frictions in the relations among agents are endogenous. Frictions are modeled as dependent on the result of a coordination game, played by every pair of directly linked agents and characterized by 2 equilibria: one efficient and the other risk dominant. The model has a multiplicity of equilibria and we produce a characterization of those are stochastically stable.
Keywords: A14; D20; J00; 330; network; decay; strategical interaction; Netzwerk; Spieltheorie; Gleichgewicht; Koordination; Theorie